Efektivitas Penyelenggaraan Otonomi Desa Dalam Rangka Pengelolaan Keuangan Desa - Ariyana Sari; Febbi Amalia; Dona Safira; Kresnawati K (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Government affairs, and also to the welfare of the community based on agreements that affect the origin and values that grow in the community by following village developments. As contained in the regulations regarding villages namely, Law No. 6 of 2014 is the starting point for villages to be able to develop, especially in conducting village financial management processes. In the process of organizing activities, especially for villages, the financial management system is in the form of funds generated from village income or expenditure (APBDes) carried out by the local village government which has the authority in implementing village autonomy. The government provides village funds to be allocated every year with a minimum proportion of 40% of the village fund allocation for each village or with a minimum of Rp. 27.2 trillion, of course the mandate for distributing this large budget is to carry out infrastructure and village development activities. Unfortunately, based on practice in the field, the use of village funds often does not feel prosperous. This is because the village government is felt to be unable to fulfill its capacity and capability and there is a lack of response or massive community participation in the village financial management process. Therefore this writing aims to find out about the role of the village government in optimizing village financial management through the distribution and use of village funds sourced from the APBN and community participation in the village financial management process. In this writing, there is a method, namely the empirical method, which is an observation that focuses on social aspects and on conditions that are the object of detailed research.